Economic and societal impact of organized crime: policy and law enforcement interventions - Danielsson, Alicia (Advances in public policy and administration (APPA) book series, 2024)
"This book, in its exploration of the multifaceted nature of serious and organized crime globally, dedicates a significant portion to examining policy and law enforcement interventions"--